2001
DOI: 10.1046/j.1365-3059.2001.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and possible origin of Amylostereum areolatum in South Africa

Abstract: The woodwasp, Sirex noctilio, and its symbiotic fungus, Amylostereum areolatum, cause extensive damage to pine plantations in the Southern Hemisphere. S. noctilio was first reported from South Africa in 1994. In this study, the population diversity of A. areolatum isolates from South Africa, South America, Australasia and Europe was determined by vegetative incompatibility testing. All 108 South African and 26 South American isolates belonged to the same vegetative compatibility group (VCG). This VCG showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
5
46
1
Order By: Relevance
“…Certain isolates from the field in Australia were found to be better for rearing the nematode than others (R. A. Bedding, personal communication in Slippers et al , 2001 ). Similarly, in South Africa, preliminary observations reveal that nematodes imported from Australia are more easily reared using the fungus imported with the nematodes than using the fungus isolated from the field in KwaZulu-Natal and Western Cape.…”
Section: Factors Influencing Successful Establishment Of D Siricidicolamentioning
confidence: 98%
See 1 more Smart Citation
“…Certain isolates from the field in Australia were found to be better for rearing the nematode than others (R. A. Bedding, personal communication in Slippers et al , 2001 ). Similarly, in South Africa, preliminary observations reveal that nematodes imported from Australia are more easily reared using the fungus imported with the nematodes than using the fungus isolated from the field in KwaZulu-Natal and Western Cape.…”
Section: Factors Influencing Successful Establishment Of D Siricidicolamentioning
confidence: 98%
“…In 2005, an established population of S. noctilio was confirmed in the United States of America ( Hoebeke et al , 2005 ). Slippers et al (2001Slippers et al ( , 2002 used vegetative compatability groups, DNA sequences and restriction fragment length polymorphism data of A. areolatum to consider the origin and S. noctilio populations. Various silvicultural practices have been recommended to minimize the impact of S. noctilio .…”
Section: Introductionmentioning
confidence: 99%
“…The high amount of VCG diversity could also be influenced by sexual reproduction of the fungus in ENA. However, fruiting bodies of A. areolatum have not been reported in North America, and are rare in the native European range [17].…”
Section: Discussionmentioning
confidence: 99%
“…Vegetative incompatibility assays using randomly selected representative samples from each identified A. areolatum mtSSU haplotype were performed using established methods to determine vegetative compatibility groups (VCGs; electronic supplementary material, S9; [17]). VCG richness was then used as an additional measure of genetic diversity.…”
Section: Methodsmentioning
confidence: 99%
“…This discovery made it possible to investigate the global spread of S. noctilio, as reflected by the fungal symbiont (101,103,114). Subsequent studies using vegetative compatibility groups, together with data from DNA sequences and PCR restriction fragment length polymorphisms, showed that a clone of the fungus had spread across three continents, presenting arguably the largest geographically spread single fungal individual ever recorded (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%